Neurilemmoma of the Parotid Gland - Islam, AKMR; Murshid, M (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Nerilemmoma is well encapsulated tumour,which forms a single, round or fusiform firm mass on the course of a nerve.They arise from Schwann cells of neurilemma of nerves. These tumors often grow to a large size without causing any neurologic deficit.We report here a case of neurilemmoma of parotid gland showing histopathological findings of cellular neurilemmoma,in a 20 year old male patient. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21010 J Bangladesh Coll Phys Surg 2013; 31: 227-229